The two cultures and a second look : - Snow, C. P. (University Press, 1964)
Since Lord Snow first used the phrase in the 1959 Rede Lecture, the concept of the "two cultures" has become part of the English language. His view on the gulf that exists between the scientist and the non-scientists has become one of the most discussed statements of our generation.